Improving ThaiLabanXML standard for the automatic Thai laban drag drop system - Yootthapong Tongpaeng (2019)
© 2019 IEEE. Thai dance has a long history in Southeast Asia. Preserving Intangible Cultural Heritage is a challenging task that requires the use of a combination of technologies to record and represent the dance as a three-dimensional human figure. The Labanotation System had been used to record many kinds of dances such as the Thai dance. To represent the Thai dance as a 3D animation based on Thai Laban Scores, the first version of ThaiDanceXML standard was developed to convert the data manually from Human-Readable data to Machine-Readable data. There are some issues occurred such as the human error regarding reading Thai Laban scores and writing ThaiLabanXML. Hence, a Thai Laban Drag Drop system has been created to reduce such issues and to assist the notator to write Laban scores by displaying the movements in a 3D human figure animation. Therefore, a new version of the ThaiLabanXML standard must be improved to support the Thai Laban Drag Drop system. This paper is focusing on improving the ThaiLabanXML standard to support the automatic Thai Laban Drag Drop system in order to write Thai Laban scores and represent the Thai dance movement in 3D animation.